Association between brain reserve proxies and clinical progression in Alzheimer's disease dementia. (December 2021) - Yoon, Hyung‐Jun; Seo, Eun Hyun
Abstract: Background: Given that dementia prevalence is getting higher around the world, it is important to make a prognosis about clinical progression after dementia diagnosis. Brain reserve theory suggests that greater reserve supports for functional adaptation to clinical progression in neurodegeneration. Therefore, we examined if reserve proxies at baseline were associated with clinical progression among Alzheimer's disease dementia (ADD). Method: We selected ADD data from Alzheimer's Disease Neuroimaging Initiative (ADNI) database. Composite FDG‐PET ROIs (angular gyri, posterior cingulate, and inferior temporal gyri; FDG ROIs), structural MRI volumes for hippocampus, entohinal, and intracranial volume (ICV), American National Adult Reading Test (AMNART) error score, functional activities questionnaire (FAQ), mini mental status examination (MMSE), and other clinical and neuropsychological data, and follow‐up data were downloaded. Clinical progression was measured by change score of clinical dementia rating sum of box (CDR SB change) between baseline and the last follow‐up. Cox proportional hazards models were conducted to investigate the associations between reserve proxies and further progression with covariates of age, gender, and MMSE. Result: We included 120 patients with ADD at baseline. Mean follow‐up month were 11.42 (5.82, range 6∼24month). Based on CDR SB change, 87 were identified as progression group, while 33 were stable group. At baseline, there were no significant group difference in demographic variables, follow‐up month, CDR SB, FDG ROIs, MRI volumes, distribution of APOE ε4 and Aß positive. However, progression group showed lower performance in AMNART and some neuropsychological tests. Among reserve proxies (education, AMNART, FDG ROIs, ICV, FAQ), FDG ROIs (HR=2.209, p=0.002, 95% CI 1.339‐3.643) was significant in the Cox proportional hazard model. This association was observed only in lager ICV group (HR=4.628, p=0.001, 95% CI 1.810‐11.837), whereas no significant association was found in smaller ICV group. Conclusion: Our findings indicate that relatively preserved brain metabolism may slow a rate of clinical progression in ADD, particularly in greater ICV group. In addition to ICV, which is widely used proxy for brain reserve, glucose brain metabolism could play a key role in functional compensation in the process of neurodegeneration.